ICONIC-CONVENTIONAL SYNCRETISM AND RITUAL-MAGICAL SEMIOSIS - Soletskyi, Oleksandr (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
Aim. The paper deals with the features of ritual-magical semiosis, structural and iconic-conventional consistency of ritual-magical formulas. The focus is on the functionality of visual analogies in interpretive strategies, and their semiotic imitation scenarios are studied. The ritual-magical expository constants are interpreted as complexes that mirror the system of structural and semiotic iconic-conventional connections and transitions of visual and verbal experience. Ritual and magical performances are interpreted as “emblematic staging” because they reproduce traditional, “edited” by time and experience conservative rites that have a fixed connotation and structure. Methods. The study relies on a system of genetic, hermeneutic, structural and semiotic methods. The author draws on the scientific methodology of semiotics and hermeneutics, and uses the methodology of literary cognitive science. This is due to the specific nature of the study, its subject of inquiry. Results. The magical and ritual complex is interpreted as the first creative comprehension of reality by a person on the basis of arbitrary associations and fantasy analogies. It marks the coordinates of the original epistemological focuses, primarily the organised interpretive practice. The visualisation and imitation of certain processes, artificial object and verbal compilation, and the combination of images and words into a single expressive complex constitute its structural integrity. It exhibit traces of emblematic comprehension and representation of ancient thought experience, where the dominant role is fulfilled by psycho-emotional observations of natural phenomena, their reduction into a special form, system of actions and speech. Sacrifices, totemism, animism, initiations, and various magical practices established the accessibility of visual-verbal syncretism for both awareness and expression. This was the format that was feasible for a common meaning making convention agreeable through “naturalistic emblematism”.